Temporal patterns of fish occurrence of the euryhaline sector of a subtropical estuary, southern Brazil - Nakayama, Paula; Peret, Alberto Carvalho; Cardoso, Olímpio Rafael; Lamour, Marcelo Renato; Spach, Henry Louis (Acta Scientiarum. Biological Sciences, 2020)
Fish fauna was studied in five sites of the shallow infralittoral of the Paranaguá Bay during the period from October 1999 to September 2000. At each sampling site, fish were sampled with other trawls, salinity and temperature were measured, water samples were taken from the bottom of the water column for determination of dissolved oxygen, dissolved inorganic nitrogen and phosphate. The spatial and temporal behavior of the environmental variables was analyzed by a Principal Component Analysis; Cluster Analysis was used to gather the sampling sites, and Factorial Correspondence Analysis was applied to the most abundant species. Temperature was the most important variable for the distribution of the months, allowing the division of the study period into hot and cold months. The temporal variation in the fish fauna composition was indicated by cluster analysis, with highest percentages of dissimilarity between the sampling sites during hot months. The variation in dissimilarity between the sites occurred due to differences in the number of individuals and species of the catches. The high frequencies of occurrence of Anisotremus surinamensis, Etropus crossotus, Genidens genidens, Micropogonias furnieri and Sphoeroides greeleyi were related to high temperatures. The greatest number of fish and species observed in hot months may be related to the life cycle of many species, which reproduce in warmer months, and whose offspring use estuaries as breeding areas.